Language Teachers as Partners in Crafting Educational Language Policies? - Shohamy, Elana (Íkala, Revista de Lenguaje y Cultura, 2009)
The paper presents an expanded view of language policy which incorporates a variety of policy mechanisms which are claimed to affect de facto language policies. These mechanisms include declared policies, language education documents, language tests and language in public space, among others. These policies are initiated and determined by ''policy bodies'' which are part of governments and other groups in authority, but are detached from those who are execute them. The main objective of this paper is to portray the expanded view of language policy, along these mechanisms, and to argue for the involvement and active participation of teachers in this process. I will argue that the participation, discussions and negotiations constitute a civic and democratic obligation on route to valid, open, fair, realistic policies. Negotiations with the different stake holders who come the process with experience and knowledge is essential for developing language policies which are valid, constructive, critically based and are based on theory of practice. Received: 24-02-09 / Accepted: 31-03-09 How to reference this article: Shohamy, E. (2009). Language Teachers as Partners in Crafting Educational Language Policies? Íkala. 14(2), pp.45-67.